Biomimetic, Mild Chemical Synthesis of Cdte-Gsh Quantum Dots with Improved Biocompatibility - Vasquez-Guzman, C; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Monras-Charles, J (2012)
Sin Editorial Disponible